A Review Thin-Wall-Tube Energy-Absorbing Structure : Crash-Box. Issue 1 (1st February 2023) - Memane, K; Mashalkar, A; Kumar, P
Abstract: The sudden impact during a collision of an automobile may cost the life of passengers. Several researchers are working to design materials and structures which can absorb impact-energy before passing it to the passengers. One such solution is the crash-box-structure which is placed primarily on the frontal side, in-between the bumper and main part of an automobile. The crash-box-structure's ability to absorb energy is influenced by its deformation-properties. Both, the crash-box-structure's shape and material will decide how it affects it's deformation. The impact of various geometries and materials on the crash-box's deformation characteristics is discussed in this article. Moreover, the use of fiber-reinforced composites in the crash-box is also discussed. The surface modification may affect the impact behavior, which is also discussed in this review.